PENGARUH KONSENTRASI CROSPOVIDONE TERHADAP MUTU FISIK SEDIAAN ORAL FAST DISSOLVING TABLETS LORATADINE HCl - Deny Budi Legowo (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2021)
Oral Fast Dissolving Tablet (OFDT) is a solid dosage form, containing an active substance which disintegrates rapidly within a few seconds when it is placed on the tongue, and generally will dissolve in less than 60 seconds. The manufacture of OFDT loratadine HCl in this formulation is to find out which results are more optimal from the different concentrations of Crospovidone disintegrants with 2%, 3%, and 4% concentrations. In this study, the method used is wet granulation, which can improve the comparability of loratadine HCl, as medicine formulations. This study aims to determine the effect of the physical quality of the Oral Fast Dissolving Tablet loratadine HCl preparation on the concentration of crospovidone as a disintegrant and to determine concentration of crospovidone that can provide results fulfilling the requirements in the manufacture of Oral Fast Dissolving Tablets. In the first formulation the average disintegration time is 0.34 minute, the second formulation disintegration time is 1.16 minute, the third formulation disintegrated time is 0.50 minute. The results of the three formulations state that only the first and third formulations accomplish the requirements, the second formulation does not accomplish the requirements. In the manufacture of OFDT preparations with different concentrations of Crospovidone, it is very influential on the disintegration time, and in this formulation, the better result is a concentration of 2% because it has a faster disintegration time and physical quality that fulfill the requirements